2006
DOI: 10.1002/cncr.22441
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib inhibits meningioma tumor growth in a mouse xenograft model

Abstract: BACKGROUND.Treatments for recurrent meningiomas are limited. We previously demonstrated universal expression of COX‐2 in meningiomas and dose‐dependent growth inhibition in vitro with celecoxib, a COX‐2 inhibitor. We therefore tested the effects of celecoxib on meningioma growth in a mouse xenograft model.METHODS.Meningioma cell lines (IOMM‐Lee, CH157‐MN, WHO grade I primary cultured tumor) were transplanted into flanks of nude mice fed mouse chow with celecoxib at varying concentrations (0, 500, 1000, 1500 pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 39 publications
1
49
0
5
Order By: Relevance
“…In the same study, using western blotting analysis, we identified that COX-1 and COX-2 protein levels were reduced in the combination group cells in comparison with those in the control group (20). The reason for the inhibition of COX-1 and/or COX-2 mRNA and protein expression in neoplastic tissues may be due to the inhibition of angiogenesis, induction of apoptosis and/or antiproliferative effects (6,8,10). The antitumor effects of coxibs have long been suggested to depend on the inhibition of COX activity and PG synthesis.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In the same study, using western blotting analysis, we identified that COX-1 and COX-2 protein levels were reduced in the combination group cells in comparison with those in the control group (20). The reason for the inhibition of COX-1 and/or COX-2 mRNA and protein expression in neoplastic tissues may be due to the inhibition of angiogenesis, induction of apoptosis and/or antiproliferative effects (6,8,10). The antitumor effects of coxibs have long been suggested to depend on the inhibition of COX activity and PG synthesis.…”
Section: Discussionmentioning
confidence: 80%
“…PGE 2 is produced from arachidonic acid by one of two enzymes: COX-1 or COX-2. There is increasing evidence that PGE 2 contributes to tumor progression by promoting tumor angiogenesis and inducing tumor cell apoptosis (8,26,27). Our same study that focused on the potential mechanisms revealed that coxibs suppress ovarian tumor growth by influencing cell proliferation and apoptosis (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factor VIII-related antigen, also known as von Willebrand factor (vWf), is synthesized in ECs and megakaryocytes and it mediates platelet adhesion to the walls of injured vessels. Immunohistochemical detection of CD31 and F VIII RAg has been used extensively to quantify angiogenesis of xenograft tumors in immunodeficient animal models carrying various human tumor cell loads (Vanzulli et al 1997, Fulzele et al 2006, Muruganandham et al 2006, Ragel et al 2007). …”
Section: Abstract and Abbreviationsmentioning
confidence: 99%
“…Las células TA3-MTX-R fueron seleccionadas a partir de un tumor ascítico TA3 in vivo, de acuerdo a lo descrito por Rosas et al (2013), en una concentración final de 2x10 6 células por mL de la suspensión tumoral. , el cual fue diluido en el agua destilada hasta alcanzar la concentración media de 1000 ppm, según lo descrito por Ragel et al (2007 Las muestras de los pulmones fueron fijados en formalina tamponada al 10 % por 48 h, realizándose el procesamiento histológico necesario para obtener cortes de 5 µm, los que fueron teñidos con H&E y Tricrómico de Arteta, según lo descrito por Rosas et al (2013). Se agregaron muestras de pulmón sano de ratón, como control.…”
Section: Materials Y Métodounclassified